Classroom Management Strategies and Demographic Predictors Among Junior High School Teachers - Marina Dwi Mayangsari; Aslamiah Aslamiah; Noorhapizah Noorhapizah; Novitawati Novitawati (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aimed to explore classroom management strategies and to identify demographic factors influencing classroom management competencies among junior high school teachers in the context of modern learning. Using a quantitative, cross-sectional survey design, data were collected from 48 public and private junior high school teachers using a validated Classroom Management Scale covering multiple dimensions of classroom practice. The findings indicate that most teachers demonstrate high levels of classroom management skills. Feedback, the creation of a conducive learning environment, and effective instructional techniques emerged as the most dominant strategies, reflecting a proactive and student-centered approach. Comparative analysis revealed that teaching experience and age had a stronger influence on classroom management competence than formal academic qualifications or employment status. Notably, the study identified a non-linear pattern of classroom management ability, which peaked at 10–20 years of teaching experience before declining at later career stages, likely due to burnout. These findings highlight the importance of differentiated professional development programs that emphasize experiential learning, mentoring, digital literacy, and teacher well-being rather than reliance on formal qualifications alone.